MEMBANGUN WIRAUSAHA DENGAN SEKOLAH WIRAUSAHA ‘AISYIYAH (SWA) KABUPATEN PEKALONGAN - Danang Satrio; Ari Muhardono (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2022)
The number of unemployed who increased by 1.84% from 2019 meant that new seeds should emerge in entrepreneurship. Entrepreneurs are important for a country because they have several benefits, including opening or providing jobs for the Indonesian people so that they are able to reduce unemployment, alleviate poverty, turn the wheel of the economy, an entrepreneur will be able to pay employees so that their families have the purchasing power to meet their needs. The existence of entrepreneurs has a role as a source of income for the government, both central and local in paying taxes, and when the product penetrates foreign countries it will strengthen foreign exchange reserves. In addition, entrepreneurs can also advance the nation through their contributions in various fields such as education, culture, health, and others. The number of entrepreneurs in Indonesia, which is apparently still low, and the current Covid-19 pandemic conditions are increasingly narrowing job opportunities, so we must be creative and innovative.Business actors are not only men but you women should also be involved. This is because entrepreneurs have more flexible working hours making it easier to manage time in taking care of the household and taking care of the business. Aisyiyah Entrepreneurial School (SWA) is a forum for women's empowerment that focuses on alleviating poverty through entrepreneurship. The current pandemic condition makes learning activities must be done online. In line with this, about 83% of women in Indonesia want online entrepreneurship training. This activity uses the method of socialization and community education with an online system, this is due to the increasing Covid-19 condition. This activity aims to help womenpreneurs to help their strengths in entrepreneurship. The material provided is very closely related to entrepreneurial activities so that female entrepreneurs become tough, never give up, creative, as well as effective and efficient.